Improving the Performance of Higher Education Academic Information Systems Using Cloud Computing Technology - Nugroho, Handoyo Widi; nurjoko, Nurjoko; Andani, Bethania (Universitas Dharma Wacana, 2023)
Improving the performance of academic information systems using cloud computing technology is very relevant and important. The application of cloud computing technology to higher education academic information systems can also help improve data security and information risk management. The research results show that cloud computing technology significantly improves the performance of academic information systems in higher education. This technology enables faster and easier access to academic information, and strengthens data management and data analysis capabilities.